ANALISIS KETEPATAN SASARAN PENERIMA BANTUAN SOSIAL PROVINSI GORONTALO - Sulistiani A Ajun; Syarwani Canon; Boby Rantow Payu (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Sulistiani A Ajun, 2024. "Analysis of the Accuracy of Targeting Social Assistance Recipients in Gorontalo Province". Development Economics Study Program, Department of Economics, Faculty of Economics, Gorontalo State University, with Supervisor, Prof. Dr. Ir Syarwani Canon, M.Si and Supervisor II Boby Rantow Payu, S, Si, ME This research aims to analyze (i) The accuracy of the distribution of Social Assistance (BANSOS) in Gorontalo province (ii) The characteristics of households receiving Social Assistance (BANSOS) in Gorontalo province. The data used in this research is secondary data sourced from the Central Statistics Agency obtained from the National Socio-Economic Survey, Household KOR, Individual KOR, and Consumption and Expenditure KOR for March 2023. This research uses descriptive analysis with the crosstabulation test (Cross Tabulation). The results of this research show that the distribution of social assistance based on data from the National Socio-Economic Survey (SUSENAS) is said to be not on target for the types of assistance from the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), Prosperous Family Card (KKS), and Direct Cash Assistance. Village Funds (BLT-DD) are different from the Smart Indonesia Program (PIP) type of assistance which is said to be right on target. Keywords: PKH, BPNT, KKS, PIP, BLT-DD